Les biens communs vécus, une finalité non utilitaire - François Flahault (Développement Durable et Territoires)
In this essay, the author discusses the notion of « lived common goods. » Lived common goods must answer three criteria : non-rivalry, non-exclusion, and third, being several persons is the condition for these goods to be produced and experienced. Further, they are immaterial. The author illustrates the notion through a series of examples, one being conversation. Finally, he shows how the notion can contribute to expand ecological thought to human psychic life.